Dietary Energy Utilization in Ongole Grade and Ongole Grade x Limousin Young Bulls Fed Napier Grass and Concentrate - E. Rianto (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2009)
ABSTRACT             An experiment was carried out to investigate the efficiency of dietary energy utilisation in Ongole Grade (OG) and OG x Limousin (OGL) young bulls under intensive feeding regime. This experiment used 4 OG and 4 OGL young bulls (about 6 months old). The initial body weight of OG was 78±4.69 kg (CV=6.01%), and that of OGL was 91.25±12.62 kg (CV=13.80%). This experiment used “Independent Sample Comparison” method. Parameters observed were energy intake, energy digestibility, energy metabolisability, live weight gain and energy conversion. The results showed that dry matter (DM) intake of  OG PO (26.87 g/ kg BB) was lower (P<0.05) than that of OGL (33.05 g/ kg BB/d); so that energy intake of OG (0.43 MJ/kg BB/d) was also lower (P<0,05) than that of OGL (0.55MJ/kg BB/d). However, were not significant difference (P>0.05) between the two breeds in all other parameters observed. Dietary energy digestibility’s in OG and OGL were 52.60 and 52.20%, respectively. Energy metabolisability’s in OG and OGL were 44.30 and 42.90%, respectively. Live weight gain of were 0.325 and 0.412 kg/d in OG and OGL, respectively Energy conversions in OG and OGL were 46.44 and 55.90 MJ per kilogram live weight gain. It was concluded that OG and OGL young bulls under intensive feeding regime had similar performance in energy utilisation.   Key words: cattle, breed, energy metabolism